Phenomenologies of violence - Staudigl, Michael, 1971- (Studies in contemporary phenomenology, 2014)
"Phenomenologies of Violence explores phenomenology's capacities to deepen our understanding of various violences. The volume presents phenomenology as an interdisciplinary, relevant method to investigate violence, its many faces, meanings, and far reaching consequences for human existence and self-understanding." -- Resumé vydavatele